BAY 81‐8973, a full‐length recombinant factor VIII: results from an International comparative laboratory field study. (31st March 2016) - Kitchen, S.; Beckmann, H.; Katterle, Y.; Bruns, S.; Tseneklidou‐Stoeter, D.; Maas Enriquez, M.
Abstract : Introduction: BAY 81‐8973 is a full‐length, unmodified, recombinant human factor VIII (FVIII) with the same primary amino acid sequence as sucrose‐formulated recombinant FVIII but produced with certain more advanced manufacturing technologies. Aim: This global laboratory study evaluated variability in measurement of BAY 81‐8973 using one‐stage and chromogenic assays compared with antihaemophilic factor (recombinant) plasma/albumin‐free method (rAHF‐PFM; Advate ® ) under assay conditions routinely used in clinical laboratories. Methods: BAY 81‐8973 or rAHF‐PFM was spiked into FVIII‐deficient plasma at 0.043 (low), 0.375 (medium) and 0.865 (normal) IU mL −1 . Participating laboratories analysed blinded samples and normal plasma in triplicate using their routine assay, reagents and standards. Results were analysed for intra‐ and interlaboratory variability. Results: Forty‐one laboratories in 11 countries participated in the study. One‐stage assay and chromogenic assays were used by 40 and 10 laboratories, respectively; 9 laboratories used both assays. Intralaboratory variability was <11% for both assays and both products at all concentrations. Interlaboratory variability was highest at the low concentration in the chromogenic and one‐stage assay for BAY 81‐8973 (60.0% and 33.7%, respectively) and rAHF‐PFM (51.0% and 30.8%) and was lowest at the normal concentration (BAY 81‐8973, 5.4% and 14.0%; rAHF‐PFM, 5.8% and 12.4%), which was similar to the plasma control (6.6% and 10.3%). The chromogenic:one‐stage assay ratio ranged from 0.95 (low concentration) to 1.10 (normal concentration) for BAY 81‐8973 and 0.96–1.18 for rAHF‐PFM. Conclusions: BAY 81‐8973 can be accurately measured in plasma using the one‐stage and chromogenic assays routinely used in clinical laboratories without a product‐specific standard.